2018
DOI: 10.1007/s12031-018-1044-z
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Monoamine Oxidase A Gene Expression by Distinct Variable Number Tandem Repeats

Abstract: The monoamine oxidase A (MAOA) uVNTR (upstream variable number tandem repeat) is one of the most often cited examples of a gene by environment interaction (GxE) in relation to behavioral traits. However, MAOA possesses a second VNTR, 500 bp upstream of the uVNTR, which is termed d- or distal VNTR. Furthermore, genomic analysis indicates that there are a minimum of two transcriptional start sites (TSSs) for MAOA, one of which encompasses the uVNTR within the 5′ untranslated region of one of the isoforms. Throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 30 publications
1
48
0
3
Order By: Relevance
“…A final interesting perspective comes from a recent investigation by Manca et al (2018). This study revealed a role of a second MAOA gene polymorphism (dVNTR) on MAO-A expression.…”
Section: Discussionmentioning
confidence: 94%
“…A final interesting perspective comes from a recent investigation by Manca et al (2018). This study revealed a role of a second MAOA gene polymorphism (dVNTR) on MAO-A expression.…”
Section: Discussionmentioning
confidence: 94%
“…VNTRs are frequently found in functional genic regions (such as coding sequence, promoter, untranslated region [UTR]) and may affect gene transcription, messenger RNA (mRNA) splicing, posttranscriptional modification or translational efficiency (Brookes, 2013). In selected cases, a causative link between their copy number and gene expression has been proved (Manca et al, 2018; van Dyck et al, 2005; Warburton, Breen, Bubb, & Quinn, 2016). Importantly, VNTRs have been correlated to human diseases (Brummett et al, 2007; Faraone, Doyle, Mick, & Biederman, 2001; Kennedy, Weed, Forget, & Morrow, 1994; Ogilvie et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Because our study is based on a case-control design, temporality could not be inferred with certainty. Another limitation present in this study is the lack of genotype data for subjects, since gene variants may influence the expression of the HTR2A gene [42][43][44] and the MAOA gene [45,46]. In this study, it was not possible to obtain the toxicological data due to legal issues and information privacy.…”
Section: Discussionmentioning
confidence: 99%